2013
DOI: 10.1590/s1516-35982013000600006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and non-genetic effects on calf vigor at birth and preweaning mortality in Nellore calves

Abstract: -The objective of the present study was to evaluate the genetic and non-genetic effects that influence vigor at birth and preweaning mortality in Nellore calves. A total of 11,727 records of births that occurred between 1978 and 2006, offspring of 363 sires, were analyzed. Poor calf vigor at birth (VB) and preweaning mortality divided into stillbirth (SB), early mortality (EM) and total mortality (TM) were analyzed as binary variables. Generalized linear models were used for the evaluation of non-genetic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
4
25
2
Order By: Relevance
“…This is consistent with a study where in a dry-tropical environment, Brahman calves that died during neonatal life were on average 6.1 kg lighter than those that survived (Muller, 2007 Schmidek et al, 2013). Therefore, the association between decreased birth vigour and increased calf mortality may be at least partly explained by low birth weight.…”
Section: Calf Ability To Sucklesupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with a study where in a dry-tropical environment, Brahman calves that died during neonatal life were on average 6.1 kg lighter than those that survived (Muller, 2007 Schmidek et al, 2013). Therefore, the association between decreased birth vigour and increased calf mortality may be at least partly explained by low birth weight.…”
Section: Calf Ability To Sucklesupporting
confidence: 91%
“…Kim et al (1988)'s report is consistent with calf autopsies where hairballs have been found in the calf abomasum, derived from hair around the udder or from the calf licking itself (Bellows et al, 1987). In studies on Bos indicus calves (n > 3000), frequency of low vigour has been reported at 4.75% in Brazilian Nellore (Schmidek et al, 2013) and 10.6% in a mixed herd of Brahman and Brahman-influenced calves (Riley et al, 2004), with other studies reporting relative frequencies of weak Brahman calves (n > 3000) within this range of values (Riley et al, 2004, Wythe, 1970. As birth vigour heritability values ranged from 0.01 to 0.09 in Nellore calves (Schmidek et al, 2013) and was 0.09 in Brahmans, management interventions may provide greater improvements in calf vigour than selection (Riley et al, 2004).…”
Section: Calf Ability To Sucklementioning
confidence: 65%
See 2 more Smart Citations
“…In Brazil, mortality rate averages of 8 and 4% were already reported for preweaning and post-weaning periods respectively (Euclides Filho, 2000). Specifically for Nellore cattle, the most important and populous zebu cattle in Brazil, losses of 6% (Corrêa et al, 2000) and 7.99% (Schmidek et al, 2013) until weaning were reported for calves in extensive breeding. Nevertheless, few quantitative studies considering preweaning mortality rate have been conducted in such breed populations.…”
Section: Introductionmentioning
confidence: 99%